Economic Evaluation of Voting Power of Common Stock - LEVY, HAIM (Journal of Finance, 1983)
ABSTRACT This paper presents an economic evaluation of common stock voting rights. An index of relative voting rights inequality for different classes of stock of the same corporation is constructed and the empirical relationship between the market premium on a superior‐voting stock and the voting inequality index is examined. In only three out of the 25 cases could investors have arbitraged between the two classes of stock, although in one case the arbitrage opportunity persisted for several months.